Lipidic nanoparticules: a model function to predict the transition temperature of DPPC-DMPC mixtures - Buffo, Flavia Edith (2017)
Thermotropic behavior of unilamellar liposomes prepared from binary mixtures of phosphatidylcholines in aqueous suspensions was analyzed by means of the temperature dependence of the Zeta Potential (ZP). This technique presents high sensitivity and small amount of sample required, that is, 70% less than that required in the use of conventional calorimeters. A model function is proposed to adjust the thermotropic behavior of the DPPC-DMPC system. From the adjustment, temperature transition (Ttransition) data as a function of the composition are obtained. The objective of this paper is to propose, from those few Ttransition-composition data, a function that allows obtaining Ttransition for any composition of the mentioned system. Moreover, graph of phase boundaries for these mixed-lipid vesicles was constructed by plotting the delimiting temperatures of the main phase transition as a function of the lipid composition of the vesicle. The combination of the zeta potential technique and the mathematical processing of their data would be a simple and useful tool for determining the transition temperatures of more complex mixtures.